2018
DOI: 10.3389/fphys.2018.01826
|View full text |Cite
|
Sign up to set email alerts
|

Long-Haul Northeast Travel Disrupts Sleep and Induces Perceived Fatigue in Endurance Athletes

Abstract: Introduction: Long-haul transmeridian travel is known to cause disruptions to sleep and immune status, which may increase the risk of illness.Aim: This study aimed to determine the effects of long-haul northeast travel for competition on sleep, illness and preparedness in endurance athletes.Methods: Twelve trained (13.8 ± 3.2 training h/week) masters (age: 48 ± 14 years) triathletes were monitored for sleep (quantity via actigraphy and quality via self-report), mucosal immunity (salivary immunoglobulin-A) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…sIgA concentrations in the present study are higher than those reported in healthy males, 44 and male competitive judo athletes, 38 but similar to those observed in trained triathletes 45 and elite female rowers. 46 It should be noted that large within and between subject variations in sIgA have been reported in sedentary and trained individuals.…”
Section: Physiological Markerssupporting
confidence: 83%
See 1 more Smart Citation
“…sIgA concentrations in the present study are higher than those reported in healthy males, 44 and male competitive judo athletes, 38 but similar to those observed in trained triathletes 45 and elite female rowers. 46 It should be noted that large within and between subject variations in sIgA have been reported in sedentary and trained individuals.…”
Section: Physiological Markerssupporting
confidence: 83%
“…These findings are supported by a previous study which reported no change in sIgA concentrations in masters level triathletes following a LH flight in a north-westerly direction. 45 These data may suggest that suppressed immunity following LH travel is associated with suppressed sAA levels, but not reduced sIgA.…”
Section: Discussionmentioning
confidence: 91%
“…The most common form of sleep assessment was subjective, with ten (27%) studies employing self-report questionnaires 26–30 , 33 , 36 , 48 , 50 , 51 and seven (18.9%) studies employing self-report sleep diaries. 32 , 34 , 35 , 39 , 49 , 54 , 57 Thirteen (35.1%) studies utilized wrist actigraphy as an objective form of sleep assessment, 5 , 6 , 24 , 25 , 31 , 37 , 38 , 40–44 , 46 whereas six studies (16.2%) used polysomnography, the gold standard in sleep assessment. 8 , 47 , 52 , 53 , 55 , 56 One study (2.7%) did not report any form of sleep assessment, however, sleep duration was controlled in a laboratory environment.…”
Section: Resultsmentioning
confidence: 99%
“…Ten (27%) studies reported the percentage of athletes who napped at least once throughout the data collection period. 5 , 6 , 25 , 26 , 29 , 34 , 36 , 39 , 41 , 60 For example, Walsh et al 41 showed that 33% of the participants (national and international level swimmers) reported napping at least once during a rest period, 75% napped during a taper period, 92% napped during a training period, and 75% napped during the competition period. Five (13.5%) studies reported the total amount of naps taken during the data collection period.…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue can be defined as “the physical and/or mental weariness resulting from exertion, that is, an inability to continue exercise with the same intensity without a resultant deterioration in performance.” 3 Therefore, fatigue applies not only to the muscular effort but also to athletes' psychology. Sleep loss exerts a negative effect on perceived effort values 4 and on cognitive and neurobehavioral performance, 5,6 resulting in a reduction in the ability to encode new information and consolidate memory 7 . Sleep loss consists of insufficient sleep continuity and/or duration.…”
Section: Introductionmentioning
confidence: 99%